Edukasi Gizi Sehat Dan Seimbang Untuk Pencegahan Stunting Pada Anak Di Wilayah Kerja Puskesmas Raya Pematangsiantar - Derma Wani Damanik; Julwansa Saragih (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Stunting is a condition where the child's body size is very low caused by inadequate nutritional intake in children for a long time due to food intake that is not in accordance with nutritional needs which has an impact on the child's short height. Stunting reflects the condition of failure to thrive in children as a result of chronic malnutrition, so that children are at risk of experiencing growth and development disorders in their lives. The incidence of stunting in Indonesia is still quite high. Nearly 9 million Indonesian children are under the age of five and are recorded to experience stunted growth. Indonesia is ranked fifth in the world for this number and more than a third of children under the age of five in Indonesia are below the average score. Based on the Nutrition Status Monitoring, the prevalence of stunting in North Sumatra in 2017 was 28.4%. The form of community service activities carried out is by providing education to the community. Educational activities are carried out for the people who are in the working area of ​​the Pematangsiantar City Public Health Center. The method used in this service activity is lectures and discussions using leaflet media. The results of community service show that before being given education the majority of participants lacked knowledge, namely 14 people (70%) while after education the knowledge of the majority of participants was good as many as 18 people (90%) which means that there was an increase in public understanding and knowledge after being given education compared to before giving education